RANCANG BANGUN ARSITEKTUR SISTEM INFORMASI MARKETPLACE JASA FOTOGRAFI BERBASIS WEB - Rani Mukherjee; Setia Gunawan, Vicky; Sri Mona Octafia (JURNAL DATA SAINS DAN TEKNOLOGI INFORMASI (DASTIS), 2025)
The fundamental issue in the photography service industry in Padang City lies in the dominance of conventional transaction mechanisms, which result in scheduling inefficiencies and low service transparency. This study focuses on the design and development of an information system in the form of a marketplace platform called Ragam Lensa as a technical solution to digitalize these business processes. The system development methodology applies a structured software engineering approach utilizing Unified Modeling Language (UML) to precisely design the data architecture and user interfaces. The system is built using dynamic web-based technologies to ensure broad accessibility for users. The outcome of this design and development process is the creation of a digital infrastructure capable of integrating portfolio search functions, real-time schedule availability validation, and accountable transaction management within a single unified ecosystem. System testing demonstrates that the architecture successfully converts manual workflows into automated processes, minimizes data redundancy, and enhances the validity of bookings. It is concluded that the development of the Ragam Lensa system significantly contributes to improving operational efficiency and strengthening the competitiveness of photography service providers through service infrastructure modernization.